2020
DOI: 10.3389/fnins.2020.00075
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structural Plasticity: From Adult Neurogenesis to Immature Neurons

Abstract: Brain structural plasticity is an extraordinary tool that allows the mature brain to adapt to environmental changes, to learn, to repair itself after lesions or disease, and to slow aging. A long history of neuroscience research led to fascinating discoveries of different types of plasticity, involving changes in the genetically determined structure of nervous tissue, up to the ultimate dream of neuronal replacement: a stem cell-driven "adult neurogenesis" (AN). Yet, this road does not seem a straight one, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 63 publications
(94 reference statements)
1
55
0
Order By: Relevance
“…Newborn neurons in both layers are later incorporated into local circuits and can be involved in analysis of olfactory information 34 , 35 . For many years, the role of adult neurogenesis is studied incessantly, and its contribution to plasticity of the brain is still reported 36 . Integration of newborn neurons into the OB circuits is required for olfactory learning 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Newborn neurons in both layers are later incorporated into local circuits and can be involved in analysis of olfactory information 34 , 35 . For many years, the role of adult neurogenesis is studied incessantly, and its contribution to plasticity of the brain is still reported 36 . Integration of newborn neurons into the OB circuits is required for olfactory learning 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Short PMI and the use of 4% PFA are considered optimal for labile antigens such as PSA-NCAM and DCX 23 , 28 . However, questions have been raised whether DCX is expressed by cell types other than immature neurons 21 , 29 , may be re-expressed in de-differentiating mature neurons 30 , or represent developmentally generated immature neurons 31 . Novel approaches 32 may be needed to resolve the issue of adult human neurogenesis.…”
Section: Adult Neurogenesismentioning
confidence: 99%
“…It also has an interaction with local alpha and beta. Ciliary genes are required for the hypothalamic accurate neuron development (Krishna and Babu, 2016;Pascoal, 2019;Rosa, 2020). It is found that the presynaptic zone is essential for axonal transport.…”
Section: Recent Findingsmentioning
confidence: 99%